2016
DOI: 10.1088/0953-2048/29/11/113001
|View full text |Cite
|
Sign up to set email alerts
|

SQUIDs in biomagnetism: a roadmap towards improved healthcare

Abstract: Globally, the demand for improved health care delivery while managing escalating costs is a major challenge. Measuring the biomagnetic fields that emanate from the human brain already impacts the treatment of epilepsy, brain tumours and other brain disorders. This roadmap explores how superconducting technologies are poised to impact health care. Biomagnetism is the study of magnetic fields of biological origin. Biomagnetic fields are typically very weak, often in the femtotesla range, making their measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 91 publications
0
54
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) at ultra-low fields has attained interest in several fields such as combining magnetic resonance imaging (MRI) with magnetoencephaolography (MEG) [1,2], resolving J-coupling structures in molecules [3,4,5], enhancing MRI contrast between certain biological tissues [6], obtaining MR image of samples enclosed in metal [7], detecting neuronal currents directly [8,9] and measuring fundamental quantities [10]. The detection of NMR signals in ultra-low fields, typically below the earth's magnetic field, requires highly sensitive sensors, such as superconducting quantum interference devices (SQUID) [11,12] or optically-pumped atomic magnetometers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) at ultra-low fields has attained interest in several fields such as combining magnetic resonance imaging (MRI) with magnetoencephaolography (MEG) [1,2], resolving J-coupling structures in molecules [3,4,5], enhancing MRI contrast between certain biological tissues [6], obtaining MR image of samples enclosed in metal [7], detecting neuronal currents directly [8,9] and measuring fundamental quantities [10]. The detection of NMR signals in ultra-low fields, typically below the earth's magnetic field, requires highly sensitive sensors, such as superconducting quantum interference devices (SQUID) [11,12] or optically-pumped atomic magnetometers [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The SQUIDs are widely used in many applications including in biomedical engineering for sensing MCG and MEG signals. Such sensitivity levels of SQUIDs require them to remain in a magnetically shielded room that is equipped with an appropriate cooling system for operation at liquid‐helium temperature 4.2 K, [ 38 ] which also increases the cost of SQUIDs to several thousands of dollars.…”
Section: Mmg Sensing Technologiesmentioning
confidence: 99%
“…It has been suggested that the weak fluctuating magnetic fields observed with MEG might be detected directly with ULFMRI from the tiny frequency shift in the signal (Neuronal Current Imaging, NCI) (Kraus et al, 2008;Cassara et al, 2008;Cassara et al, 2009;Körber et al, 2013). Although recent advances in SQUID technology have reduced the noise closer to the predicted required level (Körber et al, 2016), so far there has been no demonstration of NCI in a human brain.…”
Section: Introductionmentioning
confidence: 99%